Answer:
=5x2+5x
Step-by-step explanation:
Let's simplify step-by-step.
3x+3x2+2x2+2x
Answer:
![\displaystyle 64](https://tex.z-dn.net/?f=%5Cdisplaystyle%2064)
General Formulas and Concepts:
<u>Calculus</u>
Limits
Limit Rule [Variable Direct Substitution]: ![\displaystyle \lim_{x \to c} x = c](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20x%20%3D%20c)
Limit Rule [Variable Direct Substitution Exponential]: ![\displaystyle \lim_{x \to c} x^n = c^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20x%5En%20%3D%20c%5En)
Limit Property [Multiplied Constant]: ![\displaystyle \lim_{x \to c} bf(x) = b \lim_{x \to c} f(x)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20bf%28x%29%20%3D%20b%20%5Clim_%7Bx%20%5Cto%20c%7D%20f%28x%29)
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
![\displaystyle \lim_{x \to 0} f(x) = 4](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20%5Clim_%7Bx%20%5Cto%200%7D%20f%28x%29%20%3D%204)
<u>Step 2: Solve</u>
- Rewrite [Limit Property - Multiplied Constant]:
![\displaystyle \lim_{x \to 0} \frac{1}{4}[f(x)]^4 = \frac{1}{4} \lim_{x \to 0} [f(x)]^4](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%200%7D%20%5Cfrac%7B1%7D%7B4%7D%5Bf%28x%29%5D%5E4%20%3D%20%5Cfrac%7B1%7D%7B4%7D%20%5Clim_%7Bx%20%5Cto%200%7D%20%5Bf%28x%29%5D%5E4)
- Evaluate limit [Limit Rule - Variable Direct Substitution Exponential]:
![\displaystyle \lim_{x \to 0} \frac{1}{4}[f(x)]^4 = \frac{1}{4}(4^4)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%200%7D%20%5Cfrac%7B1%7D%7B4%7D%5Bf%28x%29%5D%5E4%20%3D%20%5Cfrac%7B1%7D%7B4%7D%284%5E4%29)
- Simplify:
![\displaystyle \lim_{x \to 0} \frac{1}{4}[f(x)]^4 = 64](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%200%7D%20%5Cfrac%7B1%7D%7B4%7D%5Bf%28x%29%5D%5E4%20%3D%2064)
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Limits
Book: College Calculus 10e
B IS THE ANSEWER TO THE PROBLEM
Answer:
g(a+1)=5a+2
Step-by-step explanation:
so (a+1) is the value of x
you can write it like this:
x=a+1
using substitution, we can swap out all 'x's for 'a+1's. like so;
g(a+1)=5(a+1)-3 -- given
=5a+5-3 -- distribute
=5a+2 -- simplify!
Hope i helped! have a great day! please mark brainliest!!